Spectrally Combined Encoding for Profiling Heterogeneous Circulating Tumor Cells Using a Multifunctional Nanosphere‐Mediated Microfluidic Platform. Issue 28 (8th May 2020) - Wu, Ling‐Ling; Zhang, Zhi‐Ling; Tang, Man; Zhu, Dong‐Liang; Dong, Xiao‐Juan; Hu, Jiao; Qi, Chu‐Bo; Tang, Hong‐Wu; Pang, Dai‐Wen
Abstract: Comprehensive phenotypic profiling of heterogeneous circulating tumor cells (CTCs) at single‐cell resolution has great importance for cancer management. Herein, a novel spectrally combined encoding (SCE) strategy was proposed for multiplex biomarker profiling of single CTCs using a multifunctional nanosphere‐mediated microfluidic platform. Different cellular biomarkers uniquely labeled by multifunctional nanosphere barcodes, possessing identical magnetic tags and distinct optical signatures, enabled isolation of heterogeneous CTCs with over 91.6 % efficiency and in situ SCE of phenotypes. By further trapping individual CTCs in ordered microstructures on chip, composite single‐cell spectral signatures were conveniently and efficiently obtained, allowing reliable spectral‐readout for multiplex biomarker profiling. This SCE strategy exhibited great potential in multiplex profiling of heterogeneous CTC phenotypes, offering new avenues for cancer study and precise medicine. Abstract : A spectrally combined encoding strategy was proposed for multiplex biomarker profiling of heterogeneous circulating tumor cells (CTCs) using a multifunctional nanosphere‐mediated microfluidic platform. Different cellular biomarkers simultaneously encoded with both magnetic tags and distinct optical signatures, enabled efficient isolation and in situ on‐chip spectrally combined encoding of heterogeneous CTCs at single‐cell resolution.